Tax Considerations in Research Grants to Faculty. - Dilley, Steven; Wheatley, John J. (The Accounting Review, 1977)
ABSTRACT: Research grants from colleges and universities may, under some circumstances, be exempt from federal income taxes. The basic requirements under the law are thoroughly discussed and the characteristics of research grants are described. Also, the excludability of grants commonly received by accounting faculty is investigated. Finally, some suggestions are made to enhance the likelihood of having research grants qualify for exclusion from taxes.